Effects of Night Work on Health Workers of Public Hospital of Pinar del Rio City, Cuba - Maria Nereyda Triguero Veloz; Jesús Carlos Gil Pérez; Tania Machín Triguero; Benardo Fernández Hernández (Psicologia, 2009)
This is a transversal descriptive study that was done to determine the effects of the night work in the health in 102 workers of the closed units (intensive Therapy and Coronary Cares) during the year 2008 in the University Hospital “Abel Santamaría” of the city of Pinar del Río, Cuba, evaluating aspects of the medical personnel’s health and paramedic after the night work, relating variables as age, sex, psychotics manifestations, stress, libido, cardiovascular dysfunctions and of the dream by means of a questionnaire carried out to a chosen personnel. Absolute frequency, percentage, media, and mode were applied to the results, being represented in graphics and squares. The feminine sex in the group of ages of 20 to 30 years prevailed between the paramedics while the group of ages from 31 to 40 years of the masculine sex it prevailed among the doctors. The psychopathological manifestation of higher incidences was the stress (66.6%). The libido didn’t modify in 85.2% of the total of the was interviewee. The tachycardia represented the biggest percent in the referred cardiovascular symptoms (54.3%). The index of drowsiness after the night labour day was expressive (89% of the sample). It was demonstrated that the hard-working doctors and paramedics of the hospital environment of intensive cares that was evaluated present a considerable number of symptoms and signs that conform morbid states that interfere in the individual’s health in the psychological, social and somatic field.